2003
DOI: 10.2105/ajph.93.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Maternal Morbidity During Labor and Delivery: United States, 1993–1997

Abstract: Maternal morbidity during delivery is frequent and often preventable. Reducing maternal morbidity is a national health objective, and its monitoring is key to improving maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 11 publications
1
69
2
4
Order By: Relevance
“…We would argue (and are supported by literature in the field) that birthweight is an inadequate proxy for 'low risk' although it is a very appealing measure because of its availability. 19,20 The low risk population in our study appeared to be a very conservative estimate, including less than 50% of the whole population of women giving birth; however, this percentage is comparable to other studies in the United States [21][22][23] and the United Kingdom. 24 Without doubt, the majority of women giving birth in the smallest hospitals represent those that live in outer regional and remote areas.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We would argue (and are supported by literature in the field) that birthweight is an inadequate proxy for 'low risk' although it is a very appealing measure because of its availability. 19,20 The low risk population in our study appeared to be a very conservative estimate, including less than 50% of the whole population of women giving birth; however, this percentage is comparable to other studies in the United States [21][22][23] and the United Kingdom. 24 Without doubt, the majority of women giving birth in the smallest hospitals represent those that live in outer regional and remote areas.…”
Section: Discussionsupporting
confidence: 68%
“…While mortality rates provide a most important measure in relation to safety, other measures of health, such as morbidity, should be included in a population-based health index in order to give an overall reflection of reproductive health. 34,35 In Australia, as in the United States and United Kingdom, the increased medical focus of maternity care delivery, although well intentioned, has resulted in rising rates of obstetric intervention [36][37][38] and in particular for low risk women, 18,39 at an increased cost to the public purse. 40 Procedures that lower risk when applied to high risk pregnancies may be counterproductive when applied to low risk women.…”
Section: Discussionmentioning
confidence: 99%
“…100 Studies have shown that women who suffered problems during a previous pregnancy were more likely to develop severe morbidity in subsequent pregnancies. 4,154,175 There is mixed evidence about ethnic inequalities in maternal death. Although our first study 160 found an association with black African and Caribbean ethnicity in the UK, Geller et al 9 did not find any association with minority ethnicity in the USA.…”
Section: Conclusion and Implications For Policy And Practicementioning
confidence: 99%
“…After the women have responded to questionnaire items, researchers and research assistants retrieved copies of the questionnaire from the women. Nine preexisting illnesses identified via literature (Zurayk et al, 1993;Danel et al, 2003;Zhang et al, 2005) were included in the questionnaire. The women were asked to indicate if they had suffered from any of the outlined illnesses six months prior to pregnancy.…”
Section: Instruments For Data Collectionmentioning
confidence: 99%
“…Existing literature includes an array of methods for identifying and classifying maternal illness. Maternal morbidities or illnesses have been grouped under various categories such as direct obstetric morbidity, indirect obstetric morbidity and psychological obstetric morbidity (Reed et al, 2000) or obstetric complications, pre-existing medical conditions (Danel et al, 2003;Berg et al, 2009) or categories of obstetric morbidity that occur during pregnancy, during delivery, or after delivery (Zurayk et al, 1993). In addition to the wide range of how maternal morbidity conditions are categorized, the methodology for detecting a maternal morbidity varied across studies as well, including interview-based diagnosis and hospital records (for example birth/hospital discharge data) (Stewart et al, 1996;Roberts et al, 2009).…”
Section: Introductionmentioning
confidence: 99%